Human Immunodeficiency Virus Infection Is Associated With Increased Meningococcal Carriage Acquisition Among First-year Students in 2 South African Universities. (5th May 2020) - Meiring, Susan; Cohen, Cheryl; de Gouveia, Linda; du Plessis, Mignon; Ganesh, Karistha; Kleynhans, Jackie; Quan, Vanessa; Tempia, Stefano; von Gottberg, Anne
Abstract: Background: Invasive meningococcal disease clusters occur among university students and may reflect higher carriage prevalence among this population. We aimed to measure meningococcal carriage prevalence, acquisition, and risk factors among first-year university students in South Africa. Methods: In summer–autumn 2017, after consenting to participate, we collected oropharyngeal swabs and questionnaires on carriage risk factors and tested students for HIV at 2 universities, during registration week (survey 1) and 6–8 weeks later (survey 2). Meningococci were detected by culture and polymerase chain reaction. Results: We enrolled 2120 students at registration. Mean age was 18.5 years, 59% (1252/2120) were female and 0.8% (16/1984) had HIV. Seventy-eight percent of students returned for survey 2 (1655/2120). Among the cohort, carriage prevalence was 4.7% (77/1655) at registration, increasing to 7.9% (130/1655) at survey 2: 5.0% (83) acquired new carriage, 2.8% (47) had persistent carriage, 1.8% (30) cleared the initial carriage, and 90.3% (1495) remained carriage free. At both surveys, nongenogroupable meningococci predominated, followed by genogroups Y, B, W, and C. On multinomial analysis, risk factors for carriage acquisition included attending nightclubs (adjusted relative risk ratio [aRRR], 2.1; 95% CI,  1.1–4.0), having intimate kissing partners (aRRR, 1.8; 95% CI,  1.1–2.9) and HIV (aRRR, 5.0; 95% CI,  1.1–24.4). Conclusions: Meningococcal carriage among first-year university students increased after 2 months. Sociobehavioral risk factors were associated with increased carriage for all analyses. HIV was associated with carriage acquisition. Until vaccination programs become mandatory in South African universities, data suggest that students with HIV could benefit most from meningococcal vaccination. Abstract : Meningococcal carriage prevalence among first-year South African university students increased over time, peaking at 8%. Human immunodeficiency virus infection was associated with carriage acquisition, while sociobehavioral risk factors were associated with carriage and acquisition. These data advocate for targeted meningococcal vaccination of students.